Factors Associated with Mortality among Patients on TB Treatment in the Southern Region of Zimbabwe, 2013. (2nd March 2017) - Takarinda, Kudakwashe C.; Sandy, Charles; Masuka, Nyasha; Hazangwe, Patrick; Choto, Regis C.; Mutasa-Apollo, Tsitsi; Nkomo, Brilliant; Sibanda, Edwin; Mugurungi, Owen; Harries, Anthony D.; Siziba, Nicholas
Abstract : Background . In 2013, the tuberculosis (TB) mortality rate was highest in southern Zimbabwe at 16%. We therefore sought to determine factors associated with mortality among registered TB patients in this region. Methodology . This was a retrospective record review of registered patients receiving anti-TB treatment in 2013. Results . Of 1, 971 registered TB patients, 1, 653 (84%) were new cases compared with 314 (16%) retreatment cases. There were 1, 538 (78%) TB/human immunodeficiency virus (HIV) coinfected patients, of whom 1, 399 (91%) were on antiretroviral therapy (ART) with median pre-ART CD4 count of 133 cells/uL (IQR, 46–282). Overall, 428 (22%) TB patients died. Factors associated with increased mortality included being ≥65 years old [adjusted relative risk (ARR) = 2.48 (95% CI 1.35–4.55)], a retreatment TB case [ARR = 1.34 (95% CI, 1.10–1.63)], and being HIV-positive [ARR = 1.87 (95% CI, 1.44–2.42)] whilst ART initiation was protective [ARR = 0.25 (95% CI, 0.22–0.29)]. Cumulative mortality rates were 10%, 14%, and 21% at one, two, and six months, respectively, after starting TB treatment. Conclusion . There was high mortality especially in the first two months of anti-TB treatment, with risk factors being recurrent TB and being HIV-infected, despite a high uptake of ART.